2020
DOI: 10.1101/2020.04.02.022681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disinhibition of the orbitofrontal cortex biases decision making in obesity

Abstract: The lateral orbitofrontal cortex (lOFC) receives sensory information about food and integrates these signals with expected outcomes to guide future actions, and thus may play a key role in a distributed network of neural circuits that regulate feeding behaviour. Here, we reveal a novel role for the lOFC in the cognitive control of behaviour in obesity. Goal-directed behaviour is biased in obesity such that in obese animals, actions are no longer influenced by the perceived value of the outcome. Obesity is asso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…Diet-induced obesity increases physical work during food seeking It has been challenging to determine whether obese animals are more or less motivated to obtain food than lean animals: on one hand, obese rodents eat more than lean rodents when food is provided freely [23][24][25] ; but on the other hand, they expend less effort to obtain food when they have to work for it [26][27][28] . This decrease in effort has primarily been observed in progressive ratio tasks that require increasing numbers of operant responses to obtain food, which we also observed (Suppl Fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…Diet-induced obesity increases physical work during food seeking It has been challenging to determine whether obese animals are more or less motivated to obtain food than lean animals: on one hand, obese rodents eat more than lean rodents when food is provided freely [23][24][25] ; but on the other hand, they expend less effort to obtain food when they have to work for it [26][27][28] . This decrease in effort has primarily been observed in progressive ratio tasks that require increasing numbers of operant responses to obtain food, which we also observed (Suppl Fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, lateral OFC is crucial for goaldirected behavior. A recent study showed how in a mouse model of obesity, lateral OFC-dependent impairments in devaluation (mediated by GABAergic transmission) may alter the ability to use the value of the outcome to guide behavior (Seabrook et al, 2023). Increased activation of OFC is also evident in drug-addicted subjects in response to drugrelated cues (Sell et al, 2000;Wang et al, 2007;Kufahl et al, 2008;Goldstein and Volkow, 2011;Ceceli et al, 2022), and it is considered an index of craving (Volkow et al, 2010).…”
Section: The Prefrontal Cortexmentioning
confidence: 99%